2022
DOI: 10.3390/ma15113807
|View full text |Cite
|
Sign up to set email alerts
|

The Triaxial Test of Polypropylene Fiber Reinforced Fly Ash Soil

Abstract: Recently, soil reinforcement using arranged or randomly distributed fibers has attracted increasing attention in geotechnical engineering. In this study, polypropylene (PP) fibers with three lengths (6, 12, and 24 mm) and three mass percentages (0.5%, 1%, and 1.5%) were used to reinforce a coal fly ash soil (FAS) mixture. Unconsolidated, undrained triaxial tests were carried out in order to study the mechanical properties of the polypropylene fiber-reinforced FAS mixture and evaluate the impact of fiber on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Li et al [9] provided an article entitled "The Triaxial Test of Polypropylene Fiber Reinforced Fly Ash Soil". Recently, soil reinforcement using arranged or randomly distributed fibers has attracted increasing attention in geotechnical engineering.…”
Section: Contributionsmentioning
confidence: 99%
“…Li et al [9] provided an article entitled "The Triaxial Test of Polypropylene Fiber Reinforced Fly Ash Soil". Recently, soil reinforcement using arranged or randomly distributed fibers has attracted increasing attention in geotechnical engineering.…”
Section: Contributionsmentioning
confidence: 99%
“…At present, most researchers at home and abroad have studied the influence of fiber reinforcement on the mechanical properties of sand by conducting triaxial compression tests [24][25][26][27][28], direct shear tests [29][30][31], and unconfined compressive strength tests [32][33][34][35] and have achieved interesting research results. The most commonly used fiber materials include polypropylene fibers [36][37][38][39], carbon fibers [40][41], and glass fibers [42][43][44][45]. Experiments indicated that increasing the length of the polypropylene fiber leads to a change in the stress-strain curve from strain softening to strain hardening [24].…”
Section: Introductionmentioning
confidence: 99%